1995
DOI: 10.1002/art.1780380706
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic osteoarthritis of the hip and bone mineral density

Abstract: Objective. To examine the cross-sectional association between radiographic features of hip osteoarthritis (OA) and bone mineral density (BMD) of the hip, spine, and appendicular skeleton among Caucasian women ages 65 and older who were participating in the Study of Osteoporotic Fractures.Methods. Pelvis radiographs of 4,855 subjects were assessed for individual radiographic features of hip OA: osteophytes, joint space narrowing, subchondral sclerosis, cysts, and femoral head deformity. Hips were graded on a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
227
2
22

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 321 publications
(268 citation statements)
references
References 51 publications
15
227
2
22
Order By: Relevance
“…The hip and knee joints have been most studied, with several groups finding evidence of higher systemic BMD in those with OA at these joint sites in a variety of populations. [7][8][9][10][11] Higher BMD has also been reported in association with OA of the spine 10,12 and hand. 9,10,13 A limitation of cross-sectional studies is that the direction of causality cannot be formally assessed.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 93%
See 4 more Smart Citations
“…The hip and knee joints have been most studied, with several groups finding evidence of higher systemic BMD in those with OA at these joint sites in a variety of populations. [7][8][9][10][11] Higher BMD has also been reported in association with OA of the spine 10,12 and hand. 9,10,13 A limitation of cross-sectional studies is that the direction of causality cannot be formally assessed.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 93%
“…14,15 It is therefore worth noting that strong positive associations between hip BMD and large joint OA have been observed in many studies, 8,10,11 and that the positive association between lumbar spine BMD and OA at both the hip and knee has been shown to persist after adjusting for the presence of spinal osteophytes. 7,10 More recently, the temporal relationship between BMD and OA has been clarified in prospective studies ( Table 2). Several longitudinal studies have shown higher BMD to be associated with a greater risk of developing subsequent radiographic knee OA, [16][17][18][19][20] although findings have not always been conclusive.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 99%
See 3 more Smart Citations